NON-TRADITIONAL METHODS OF INTEGRATING RATIONAL FUNCTIONS - Olimnazar Begaliyev; Olimnazar Begaliyev (European Journal of Humanities and Educational Advancements, 2021)
The article discusses various non-traditional methods of integrating rational functions. Using these methods, the integration of correct and incorrect fractions as well as rational functions is reduced to the integration of simple expressions. Achieving the ultimate whole is simplified